2020
DOI: 10.1021/acs.analchem.0c00524
|View full text |Cite
|
Sign up to set email alerts
|

Inexpensive Ultrasonic Nebulization Coupled with Direct Current Corona Discharge Ionization Mass Spectrometry for Liquid Samples and Its Fundamental Investigations

Abstract: The concept of direct mass-spectrometric analysis, especially exploited by ambient desorption/ionization (ADI) methods, provides numerous means for convenient sample analysis. While many simple and versatile ionization sources have been developed, challenges lay in achieving efficient sample introduction. In previous work, a sample introduction method employing direct current corona discharge (CD) coupled to a surface acoustic wave nebulization (SAWN) device enhanced sampling performance for both polar and non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“…It is found that this spectrum resembles spectra obtained from SCGD. 46,47 The main spectral features are the emission bands of OH, with band head at 306 nm, which are likely from the dissociation of H 2 O, and the N 2 second positive system, with band heads from 337.1 to 405.9 nm. The emission lines of O at 776.4 and 844.1 nm can also be observed.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…It is found that this spectrum resembles spectra obtained from SCGD. 46,47 The main spectral features are the emission bands of OH, with band head at 306 nm, which are likely from the dissociation of H 2 O, and the N 2 second positive system, with band heads from 337.1 to 405.9 nm. The emission lines of O at 776.4 and 844.1 nm can also be observed.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…An ultrasonic nebulizer (USN) was used to generate analyte-containing droplets (1–3 μm diameter based on calculation). , These droplets were transferred through a 26 kHz laser-induced plasma (LIP) in the open air toward the inlet capillary of a high-resolution Orbitrap (Exactive, Thermo Scientific, Bremen, Germany) mass spectrometer through a venturi flow guide ( cf ., Figure S1). Here, the LIP was used as an ionization source, while the USN merely served to introduce samples .…”
Section: Experimental Sectionmentioning
confidence: 99%
“…In addition to tissue analysis, ultrasonic vibration has also been used for desorption of dried samples on plastic substrate, 22 sputtering of liquid samples, 23 and extraction and nebulization of herbal products. 24 In this study, a new ionization interface coupled with online MS analysis was developed for ultrasonic sputter desorption (USD), in which a cutter applied with 40 kHz high-frequency ultrasonic vibration was used for tissue sampling.…”
Section: ■ Introductionmentioning
confidence: 99%